Freedom of expression of judges on social media - Fajdiga, Mohor (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2023)
A local court judge labelled the Slovenian Prime Minister a “great dictator” on her closed Facebook profile. One of her virtual friends captured a print-screen, propelling the posts into a national scandal. The Disciplinary Court acquitted the judge. The Ethical commission did not pass judgment on her, issuing only non-binding guidelines for public expression of judges on social networks. Nevertheless, the judge suffered significant sanctions. The President of the local court removed her from the leadership position, and she received serious threats and insults by private actors. The case note discusses the broader questions emerging from the case. In relation to which topics can judges express opinions of political nature? Can they expect privacy when they engage in closed social media communication? Which standards should the national authorities employ in assessing these issues? How judges perceive different sanctions and what measures can mitigate the chilling effect such sanctions can create? By analysing both formal and informal responses to the controversial Facebook posts and drawing upon the personal recollections of the affected judge, this case note aims to provide more clarity on the issues relevant way beyond Slovenia.
Keywords: družbena omrežja; Facebook; kazenske sankcije; sodniki; sodstvo; svoboda izražanja; zasebnost